Developing world class operations in a local bank an industry analysis and benchmarking study on contact center operations - Matanguihan, Charisse Derecho; Talisayon, Serafin D. (Quezon City University of the Philippines Diliman, 2014)
Developing world class contact center operations in a local bank is the ultimate goal of this study. The main problem being addressed is what technologies and best practices the Bank can adopt to upgrade its contact center operations to world class standards. Through competitive and international benchmarking, best-in-class and world class companies' technologies and best practices are collected, which may be used as baseline for the local bank's roadmap is achieve its ultimate goal. Given the limited time and resources allotted for this project, the research relied on the initial study conducted by the Bank's contact center head for the competitive benchmarking and on publicly available materials from different internet sources for the international benchmarking. Surprisingly, a rich literature on contact center industry trends, challenges, technologies and best practices have been published by industry experts, technology providers and consulting firms. An initial situational analysis was also conducted to document the existing operations of the Bank's contact center to facilitate comparison with local and international benchmarks. The results show that there is a wide disparity in the performance of the Bank's contact center operations compared to top local bank's contact centers. Thus, it is recommended that the Bank use this research to craft a roadmap that will define its short-term and long term plans to upgrade the contact center's operations through improvements in strategy, process, technology and people management. Furthermore, the international benchmarks provide a wide range of innovative ideas that hopefully will inspire and guide the Bank towards attainment of its ultimate goal-world class operations.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Banks and banking; Community banks; Banks and banking -- Customer services; Benchmarking; Call centers